Extracellular Vesicles: Recent Developments in Aging and Reproductive Diseases - Liu, Yu; Shen, Qiuzi; Zhang, Ling; Xiang, Wenpei (Frontiers in Cell and Developmental Biology, 2020)
Extracellular vesicles (EVs), present in cell culture media and several body fluids, play a prominent role in intercellular communication under physiological and pathological conditions. We performed a systematic literature search to review evidence regarding the existence, composition, and release of different EVs, as well as the biomarkers, cargos, and separation methods. We also reviewed the potential of EVs to transport cargos and alter the function and phenotype of recipient cells associated with aging and reproductive diseases, including polycystic ovary syndrome and endometriosis. In aging, EVs promote inflammatory reactions and offsetting the occurrence of aging. In the polycystic ovary syndrome and endometriosis, EVs and their cargos are involved in the occurrence of diseases, therapeutic strategies, and perform as non-invasive biomarkers. As the study of EVs is still in the early stages, it is not surprising that most of the current literature only describes their possible roles.